Armenia : The Road to Sustained Rapid Growth-Cross-Country Evidence - Iradian, Garbis (IMF Working Papers; Working Paper ;, 2003)
This study examines the growth determinants and the economic policy challenges that Armenia faces to sustain the rapid growth of the past two years. The paper also seeks to answer the following two questions: Why has Armenia performed relatively better than other transition economies? What are the roles of macroeconomic policies and the level of financial intermediation in explaining growth differences? The paper also draws upon past cross-country experiences by estimating panel regressions on the determinants of growth to make predictions for the Armenian economy.